Advanced bioceramics in nanomedicine and tissue engineering special topic volume with invited peer reviewed papers only - Vallet-Regí, Maria; Vila, M. (Trans Tech Publications, 2010)
Nanoscience is revolutionizing the design of medical devices, tissue scaffolding and drug-delivery systems.²⁶ New discoveries regarding nano-system, made in other research areas, have opened up the possibility of using them in biomedicine. However, such nanoscience and its possibilities, which sometimes border on science fiction, have to be kept in perspective so as not to lose sight of the limitations with respect to safety that applications within the human body impose. Nevertheless, nanomedicine focuses nowadays upon the treatment of cancer, upon tissue regeneration, and upon diagnosis and imaging. The main goal of this book is to bring together some of the advanced new trends in biomedicine that involve potential nano candidates for future treatments in the control of biological systems and in regenerative medicine. It will become an essential guide to the subject.
Keywords: Nanomedicine.; Ceramics in medicine.; Tissue engineering.; elektronické knihy; electronic books